Monitoring Endothelial and Tissue Responses to Cobalt Ferrite Nanoparticles and Hybrid Hydrogels. - Federica Finetti; Erika Terzuoli; Sandra Donnini; Marianna Uva; Marina Ziche; Lucia Morbidelli (PLoS ONE, 2016)
Iron oxide nanoparticles (NPs) have been proposed for many biomedical applications as in vivo imaging and drug delivery in cancer treatment, but their toxicity is an ongoing concern. When NPs are intravenously administered, the endothelium represents the first barrier to tissue diffusion/penetration. However, there is little information about the biological effects of NPs on endothelial cells. In this work we showed that cobalt-ferrite (CoFe2O4) NPs affect endothelial cell integrity by increasing permeability, oxidative stress, inflammatory profile and by inducing cytoskeletal modifications. To overcome these problems, NPs have be loaded into biocompatible gels to form nanocomposite hybrid material (polysaccharide hydrogels containing magnetic NPs) that can be further conjugated with anticancer drugs to allow their release close to the target. The organic part of hybrid biomaterials is a carboxymethylcellulose (CMC) polymer, while the inorganic part consists of CoFe2O4 NPs coated with (3-aminopropyl)trimethoxysilane. The biological activity of these hybrid hydrogels was evaluated in vitro and in vivo. Our findings showed that hybrid hydrogels, instead of NPs alone, were not toxic on endothelial, stromal and epithelial cells, safe and biodegradable in vivo. In conclusion, biohydrogels with paramagnetic NPs as cross-linkers can be further exploited for antitumor drug loading and delivery systems.